ECOS PASCALIANOS NA DESCRIÇÃO DA CONDIÇÃO HUMANA EM MEMÓRIAS PÓSTUMAS DE BRÁS CUBAS, QUINCAS BORBA E DOM CASMURRO, DE MACHADO DE ASSIS - FUCHIGAMI, IVNA MAIA (2019)
The present doctoral dissertation intends to approach human condition under Blaise Pascal’s viewpoint, which influenced and inspired the Brazilian writer Machado de Assis. Both perceived human being struggling among divertissement, ennui, concupiscence and vanity. Although it refers to a philosopher from the XVII century and a writer from the XIX century, there are many common aspects between them as each one, at his own way, observed human soul, full of contradiction, misery, uncertainty. For both, human condition is permeated by contradiction and irony provided by life; if someone seeks truth, he or she will find only misery and death. Machado de Assis and Blaise Pascal pointed human being’s degeneration and place their readers in a whirlpool that lead them to think and to discern, which implies suffering. For both the writer and the philosopher, human being is chaotic, miserable, contradictory, moving from need and ennui. Aware that it is useless to pretend that nothing can be seen, both guide us to distinguish, to have good jugdment. It is within this hypothesis that, based on the understanding about human condition, Machado de Assis is so inspired by the writings and thoughts of Blaise Pascal that he integrates his language partly in his work. The assumed hypothesis is the presence of similarities between a French philosopher from the XVII century and a Brazilian writer’s from the XIX century viewpoint. Therefore, the method used was a thorough search in bibliography in order to list the thoughts of Pascal that can be perceived in the three Machadian works, Memórias Póstumas de Brás Cubas, Quincas Borba and Dom Casmurro, that embody the object of this doctoral dissertation in order to prove the above mentioned hypotheses. Subsequently, it was performed a detailed reading of Pensées and the three works. The purpose was to confirm where it was feasible to perceive the concepts of divertissement, ennui, concupiscence and vanity. Machado de Assis as well as Blaise Pascal considered human being was made of incoherence and tragical contradiction, lacking of any kind of support or moral safety. Pascal summons the coming of a moral being, who is the one that feels guilty. In Memórias Póstumas de Brás Cubas, Quincas Borba and Dom Casmurro, the characters are deprived of guilt and, thus are not aware of the Fall. Machado de Assis analyzed human being in his/her insufficiency, contingence, without emotional or apologetic speech, inspired by Blaise Pascal in order to explain human condition. For that purpose, the works Memórias Póstumas de Brás Cubas, Quincas Borba and Dom Casmurro had been selected as those books are plenty of the idea that human being, according to Pascal’s thoughts, is ill and in decay. As specific authors, Blaise Pascal, Machado de Assis, Vincent Carraud, Luiz Felipe Pondé, Alfredo Bosi and Afrânio Coutinho